Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4049/jimmunol.1203552
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Effector CD4 T Lymphocytes School Lamina Propria Dendritic Cells To Transfer Innate Tolerance

Abstract: Dendritic cells (DCs) have been shown to play a major role in oral tolerance and this function has been associated with their ability to produce anti-inflammatory cytokines and to induce suppressive T regulatory cells. Herein, we demonstrate that upon oral administration of Ag, lamina propia (LP) DCs engage specific T cells and acquire a novel mechanism by which they transfer tolerance against diverse T cell specificities. Indeed, when Ig-MOG carrying the myelin oligodendrocyte glycoprotein (MOG)35–55 epitope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The onset of EAE in C57BL/6 mice induced for disease with 300 μg MOGp usually manifests around day 10 post-immunization (23). However, when a similar disease induction regimen was applied to 13R -/- mice, the clinical signs of paralysis manifested as early as day 6 post-immunization while 13R +/+ control mice had disease onset around day 10 as is typical in our mouse colony (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of EAE in C57BL/6 mice induced for disease with 300 μg MOGp usually manifests around day 10 post-immunization (23). However, when a similar disease induction regimen was applied to 13R -/- mice, the clinical signs of paralysis manifested as early as day 6 post-immunization while 13R +/+ control mice had disease onset around day 10 as is typical in our mouse colony (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MOG peptide (MOGp) encompassing aa residues 35-55 of MOG which is encephalitogenic in C57BL/6 mice (23) was purchased from EZBiolab (Westfield, IN). I-A b tetramer containing MOG aa 38-49 (MOG tet ) was obtained from NIH Core Tetramer Facillity (Emory University, Atlanta, Georgia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal study protocol (VD2153.2) was approved by the Service Vétérinaire du Canton de Vaud, Switzerland (Figure 1A). The C57BL/6J CRL mice strain was chosen because it has been successfully used in OVA-induced food allergy and oral tolerance models [32,33,34,35,36]. Briefly, 5-week-old C57BL/6J CRL female mice (Charles River Laboratories, Lyon, France) were sensitized using two subcutaneous injections of 100 µg (Sigma) and 1 mg aluminum hydroxide (Sigma) in 50 µL of phosphate buffer saline (PBS; Sigma) on two separate sites (neck and back) at days 13 and 26.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we have shown that Ig-MOG and Ig-PLP1 are effective against EAE induced by MOG and PLP1 peptide, respectively (Cascio et al, 2013, Divekar, Haymaker, 2011, Legge et al, 2001, Legge, Gregg, 2002, Legge, Min, 2000). Also, both chimeras were able to display bystander suppression and modulate CNS homogenate-induced EAE which involves multiple epitopes and diverse T cell specificities.…”
Section: Discussionmentioning
confidence: 98%